Clinical utility of esomeprazole for treatment of gastroesophageal reflux disease in pediatric and adolescent patients - Cardile S; Romano C (Dove Medical Press, 2012)
Sabrina Cardile, Claudio RomanoDepartment of Pediatrics, University of Messina, ItalyAbstract: Gastroesophageal reflux is a common condition in the pediatric population, with an increasing incidence in the last few years. It can be defined as an effortless retrograde movement of gastric contents into the esophagus related to complex multifactorial pathogenesis, involving anatomical, hormonal, environmental, and genetic factors. In some cases, it may be associated with esophageal or extraesophageal symptoms (heartburn and regurgitation), and is defined as gastroesophageal reflux disease (GERD). The therapeutic approach to gastroesophageal reflux in infants and children is often conservative, including changes in lifestyle (eg, posture and thickening of meals). If these children remain symptomatic after lifestyle changes (nutrition, feeding, and positional modification), or present with clinical red flags (poor weight gain, recurrent respiratory symptoms, or hematemesis) and complications of GERD (esophagitis, bleeding, stricture, Barrett's esophagus, or adenocarcinoma) it may be necessary to set up a proper diagnostic protocol. Proton pump inhibitors have been recommended as the most effective acid suppression therapy for adults and pediatric patients. Esomeprazole, the S-isomer of omeprazole, is the only single-isomer proton pump inhibitor available. The paper assesses the safety and tolerability of esomeprazole in pediatric and adolescent patients.Keywords: esomeprazole, gastroesophageal reflux disease, pump proton inhibitors